1 - Research-based Honours Degrees: The Perspective of Bachelor of Commerce Students at the University of South Africa - Antwerpen, Sumei van; Ferreira, Edmund (Journal of Higher Education in Africa, 2022)
The study was conducted among Bachelor of Commerce Honours students at the University of South Africa, an open distance learning institution. The main problem pertains to the reasons students pursue this degree, the value and significance of the degree as well as the reasons for doing the honours degree instead of a postgraduate diploma in a similar field of study. The most important reasons found for doing the BCom Honours degree were that it would improve future job perspectives, that the field of study was interesting and that having the degree would make one eligible for a master’s degree. It seems that the ‘image’ of obtaining an honours degree is an overriding factor in choosing the honours qualification above the postgraduate diploma. The BCom Honours degree should be marketed and presented simultaneously with postgraduate diplomas, so that prospective students can make more informed decisions to meet their specific needs. Policy makers should consider making the research modules optional for the honours degree. This initiative would give all students the opportunity to obtain an honours degree with the required modules that meet their career as well as personal needs.